IDENTIFIKASI PENINGKATAN KEBERFUNGSIAN SOSIAL DAN PENURUNAN RISIKO BUNUH DIRI BAGI PENDERITA GANGGUAN KESEHATAN MENTAL BIPOLAR DISORDER DI KOTA MEDAN MELALUI TERAPI PENDAMPINGAN PSIKOSOSIAL - FRANKY FEBRYANTO BANFATIN (Welfare StatE, 2013)
Bipolar Disorder is a mental illness that has strong influence to reduce s ocial functioning and increase risk of suicide. One way of recovery Bipolar Disorder is by means of Assistance Psychosocial Therapy. The goal of this research is to identify models of Assistance Psychosocial Therapy that can improve social functioning and reduce the risk of suicide. The type of research is a descriptive study using a qualitative approach. Research subjects were five people with bipolar disorder along with their care giver on Community Care of Schizoprenia in Medan. Analysis technique using flow models and interactive models of Miles and Huberman version. Based on the results of research, it was found that effective models to improve social functioning people with bipolar disorder are: psychoeducation, Affection-Based Family Therapy,Coping Techniques Together, Advice Friends and Friends of Control, and Support Group. The effective models to reduce the risk of suicidal patients with bipolar disorder are: Affection-Based Family Therapy, Spiritual Technique, Self Management, Coping Techniques Together, Advice Friends and Friends of Control, and Support Group. Key Words: Identification, Social Functioning, The Risk of Suicidal, Assistance Psychosocial Therapy, Bipolar Disorder